History Breaks Down into Images: Virginia Woolf’s Monk’s House Albums - Adèle Cassigneul (Études Britanniques Contemporaines, 2025)
Writing personal or collective history entails compiling archival evidence, tenuous traces of one’s past life. It means to ‘salvage something from time’ (Annie Ernaux) and recover the present of past temporalities to uncover and clarify them. In this essay, I explore, in their relation to Woolf’s literary and political representation of history, Woolf’s photographic albums, that is a personal archive she compiled and organised throughout her life as ‘the Stephen and Woolf family archivist’ (Neverow) and historian. Through cultural theories of image (Warburg, Benjamin, Didi-Huberman), my aim is to see in what ways this bulk of factual documents provided Woolf with material for the writing of her personal memoir, her fiction (Night and Day, Mrs Dalloway) and her essays (Three Guineas). I analyse how, relying on photography’s inherent historicity, Woolf pictures historical gestures that subvert linear chronologies and patriarchal monumental rhetoric.